1977
DOI: 10.1136/gut.18.6.468
|View full text |Cite
|
Sign up to set email alerts
|

Effect of secretin on plasma motilin in man.

Abstract: SUMMARY Graded doses of 0 1, 0*3, 0 9, and 2-7 clinical units/kg/h of pure synthetic secretin were infused over 60 minute periods in six healthy volunteers. Duodenal bicarbonate output and pH were recorded and plasma secretin and motilin levels were measured by radioimmunoassay. During the infusions plasma motilin fell in a dose dependent manner to a nadir of 35 %. This fall was linearly correlated with pancreatic bicarbonate output, whereas a non-linear correlation was observed between plasma motilin and both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1977
1977
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…Notably, previous studies have reported that secretin does not affect serum MLN levels in dogs (Lee et al, 1980;Poitras et al, 1993). In this review and in Deloose et al (2019), however, secretin showed a negative correlation with serum MLN levels, and this result has been replicated in a study using pigs and in human clinical studies (Mitznegg et al, 1977;Jenssen et al, 1986;Dong et al, 2012).…”
Section: Correlation Between Biochemical Findings and Mln Levelssupporting
confidence: 68%
“…Notably, previous studies have reported that secretin does not affect serum MLN levels in dogs (Lee et al, 1980;Poitras et al, 1993). In this review and in Deloose et al (2019), however, secretin showed a negative correlation with serum MLN levels, and this result has been replicated in a study using pigs and in human clinical studies (Mitznegg et al, 1977;Jenssen et al, 1986;Dong et al, 2012).…”
Section: Correlation Between Biochemical Findings and Mln Levelssupporting
confidence: 68%
“…The duodenectomy also decreased plasma motilin level only in part (271). This may further confirm that there is still another pathway for the motilin action and the source of motilin release, since in the postprandial period, nutrients and hormones, such as secretin or pancreatic polypeptide (PP), can hamper motilin-evoked effect (37,126,172). There are several reasons to assume that motilin release from endocrine cells, in response to various regulatory factors, can be amplified by intestinal contractions.…”
Section: Motilinmentioning
confidence: 80%
“…A small reduction occurs after the administration of glucose, but lipids markedly increase the release of motilin ( Mitznegg et al, 1976 ). Other hormones such as insulin, SST, and secretin reduce motilin levels ( Mitznegg et al, 1977 ; Jenssen et al, 1984 ; Jenssen et al, 1986 ). In the gastrointestinal tract, motilin increases the pressure of LES, initiates gastric phase III contractions of the MMC, stimulates gastric emptying, inhibits gastric accommodation and increases rectal compliance in humans ( Domschke et al, 1976 ; Bormans et al, 1987 ; Peeters et al, 1992 ; Kamerling et al, 2003 ; Cuomo et al, 2006 ).…”
Section: Motilinmentioning
confidence: 99%